H3N2 Virus as Causative Agent of ARDS Requiring Extracorporeal Membrane Oxygenation Support. (9th January 2014) - Peris, Adriano; Zagli, Giovanni; Bernardo, Pasquale; Bonacchi, Massimo; Cozzolino, Morena; Perretta, Lucia; Azzi, Alberta; Cianchi, Giovanni
Abstract : Pandemic influenza virus A(H1N1) 2009 was associated with a higher risk of viral pneumonia in comparison with seasonal influenza viruses. The influenza season 2011-2012 was characterized by the prevalent circulation of influenza A(H3N2) viruses. Whereas most H3N2 patients experienced mild, self-limited influenza-like illness, some patients were at increased risk for influenza complications because of age or underlying medical conditions. Cases presented were patients admitted to the Intensive Care Unit (ICU) of ECMO referral center (Careggi Teaching Hospital, Florence, Italy). Despite extracorporeal membrane oxygenation treatment (ECMO), one patient with H3N2-induced ARDS did not survive. Our experience suggests that viral aetiology is becoming more important and hospitals should be able to perform a fast differential diagnosis between bacterial and viral aetiology.